PENGARUH LINGKUNGAN KERJA DAN KEPEMIMPINAN TERHADAP SEMANGAT KERJA DAN KINERJA PEGAWAI DI LINGKUNGAN DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN INDRAGIRI HULU - Wiwin Candra; Indra Prasetyo; Woro Utari (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
The purpose of this study is to know and analyze the work environment to employee morale and performance of employees of Education and Culture Office of Indragiri Hulu Regency. In addition, to know and analyze the performance, performance, employees, employees, employees, employees, employees, employees, employees and employees. This type of research is explanatory research (explanatory research) and in this research is quantitative approach. The population in this study is the employees of Education and Culture Office of Indragiri Hulu Regency as many as 66 people and the sample in this study ruled 65 people. Data analysis was done by path analysis. The results showed the work environment, leadership, spirit and performance at the Department of Education and Culture of Indragiri Hulu Regency in good category. Work environment has a significant effect on morale. Leadership has no significant effect on morale. Work environment has a significant effect on employee performance. Leadership has a significant effect on employee performance. Work environment does not significantly affect employee performance through employee morale. Leadership has a significant effect on employee performance through employee morale Keywords: work environment, leadership, workplace, performance